Ecoprint as a Project-Based Learning Tool to Enhance Elementary School Students’ Creativity - Sinto, Susintowati; Mahfud, Mahfud; Santi, Triana Kartika Santi (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low creativity of elementary school students, where teachers experience difficulties in developing contextual and applicative learning media. This study aims to analyze the application of ecoprint integrated with Project-Based Learning (PBL) as a strategy to increase creativity, critical thinking, collaboration, and ecological awareness of students. The research subjects consisted of 25 students in grade V and 2 accompanying teachers who were actively involved in the activity. Using descriptive qualitative methods in a naturalistic setting, data were collected through participatory observation, semi-structured interviews, and documentation of student work. Data analysis is carried out inducively through the stages of reduction, presentation, and conclusion drawn, and strengthened by triangulation of techniques, sources, and time to ensure validity. The results of the study show that ecoprints are effective in fostering originality, flexibility, and elaboration in creative expression, while strengthening students' critical thinking and reflective learning skills. The project encourages intrinsic motivation, collaboration, and ecological awareness through direct engagement with natural materials, with teachers playing the role of facilitators of meaningful learning. Despite the constraints on time allocation and material availability, ecoprint has proven to be an innovative and sustainable learning medium for primary education.